The impact of COVID-19 prevention measures on epidemiology of orthopedic injuries: the outbreak ages fractures! Epidemiologic changes of fractures during COVID-19 outbreak. - Costa, Giuseppe Gianluca; Fanzone, Giuseppe; Graceffa, Angelo; Lauria, Michele; Zocco, Gianluca; Cassarà, Antonino; Campailla, Alberto; Saccà, Alessia; Santanna, Enrico; Caputo, Gianclaudio; Russo, Arcangelo (Acta Biomedica Atenei Parmensis, 2020)
Background: The application of stringent prevention measures for contrasting COVID-19 spread generated changes not only in the outbreak course, but also in epidemiology of traumatic fractures. The aim of this study was to report the epidemiologic characteristics of surgically-treated fractures during the COVID-19 outbreak over a six-month period, and to describe the variation in volumes and types of injuries, by comparing them with fractures which occurred during the same period in 2019.Methods: We retrospectively analyzed all surgically-treated fractures which were admitted from the January 1st 2020 to June 30th 2020, and compared these data to those of the corresponding timeframe in 2019. The collected data of interest included demographics, such as age and gender, fracture location, time lapse between presentation at Emergency Department and admission in the ward, length of stay.Results: A total of 117 patients were admitted with a diagnosis of facture and surgically treated, with no cases of COVID-19 positive patients. In the corresponding period of 2019, the number of patients admitted for the same reasons was 129. This decrease was more significant in the period between March and April (-30.6%), during which time prevention measures were more stringent. The only statistically significant discrepancy between the two study groups was the mean age, which was significantly higher in 2020. The location of examined injuries were similar in the two study groups, with proximal femur fractures representing the most frequent injuries.Conclusions: This study demonstrated significant changes of epidemiologic patterns of fractures during COVID-19 outbreak. These data should provide support for clinicians and government to evaluate the management and prevention strategies of traumatic not only during outbreak but also in non-outbreak period.